Preparing Children with Disabilities for Life - Cimera, Robert Evert (Rowman & Littlefield Publishers, 2002)
Educating students with disabilities is a team process. By federal law, parents must be involved in the development of their child's educational plan. Unfortunately, few parents (or regular educators) understand special education_its terms, philosophies, and processes. This book explains, in layperson terms, what special education is and how to make the special education process more successful for everyone involved. Chapters cover history and legalities of preparing children with disabilities for life, transition of families, preparation for employment, residential living, community adjustment, recreation, interpersonal relationships, life-long learning, and developing educational plans. Hundreds of additional resources for parents of children with disabilities including lists of professional organizations, useful websites, support groups, and other books for further learning on special education are also provided. While intended for parents and family members of children with disabilities, it will also be of interest to educators who are unfamiliar with special education as well as special educators who are new to the field.